V. S. Khromchenko's coastal explorations in southwestern Alaska, 1822 / Fieldiana, Anthropology, v. 64 - Khromchenko, V. S. (Vasiliy Stepanovich); VanStone, James W. editor; Kraus, David H. translator; Williams, Patricia M. editor Managing Editor, Scientific Publications ([Chicago] Field Museum Press, 1973)
Includes bibliographical references (p. 37-39, 94-95). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).